Effect of Knee Angle, Contractile Activity, and Intensity of Force Production on Vastus Lateralis Stiffness: A Supersonic Shear Wave Elastography Pilot Study - Rute Santos; Maria João Valamatos; Pedro Mil-Homens; Paulo A. S. Armada- (MDPI AG, 2024)
Supersonic shear image (SSI) ultrasound elastography provides a quantitative assessment of tissue stiffness using the velocity of shear waves. SSI's great potential has allowed researchers in fields like biomechanics and muscle physiology to study the function of complex muscle groups in different conditions. The aim of this study is to use SSI to investigate changes in the stiffness of the vastus lateralis (VL) muscle as a consequence of passive elongation, isometric contraction, and repeated muscle activity. In a single session, 15 volunteers performed a series of isometric, concentric, and eccentric contractions. SSI images were collected from the VL to assess its stiffness before and after the contractions and at various knee angles. Two-way within-subjects ANOVA was used to test the effects of muscle contraction type and knee angle on VL stiffness. Linear regression analysis was employed to assess the relationship between muscle stiffness and the intensity of isometric contractions. After maximal contractions, VL stiffness increased by approximately 10% compared to baseline values, and following maximal isometric (p < 0.01) and eccentric contractions (p < 0.05). Yet, there was no change in VL shear modulus at the end of concentric contractions. The relaxed VL shear modulus increased with knee flexion both before and after the knee extensor contractions (p < 0.001). A linear relationship between the shear modulus and the degree of isometric contraction was observed, although with notable individual variation (R2 = 0.125). Maximal contractile activity produces modest increases in relaxed muscle stiffness. The SSI-measured shear modulus increases linearly with the degree of isometric contraction.